THE COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN REGIONAL DEVELOPMENT BANKS IN JAVA AND BORNEO FOR THE PERIOD 2019-2023. - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2025)
The banking sector has undergone a substantial transformation. The industry has shifted towards digital and automated systems, thereby promoting increased operational efficiency and enhanced customer service. Regional Development Banks (RDBs) are progressively faced with the necessity to adapt and evolve in response to rapid technological innovations, changing market dynamics, and intensifying competition within the financial services landscape. This research aims to undertake a comparative analysis of the financial performance of RDBs located in Java and Borneo during the timeframe from 2019 to 2023. Furthermore, this study employs a comparative methodology to evaluate the financial performance of RDBs in Java and Borneo utilizing CAR, NIM, NPL, and ROA ratios. The findings of this research reveal a significant disparity in financial performance concerning the NIM ratio of RDBs in Java and Borneo. Conversely, there is no significant variance in financial performance regarding the CAR, NPL, and ROA ratios of RDBs in Java and Borneo.